BIPA LEARNING MEDIA: MANAGEMENT AND PROBLEMS - Ni-meenah Dereh (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
Learning media has an understanding of tools in the learning process both inside and outside the classroom. Media is a teacher teaching aid (teaching aids), can be a visual aid or other tool that can provide concrete experiences to students. Now media is a tool that is integrated in the teaching and learning process, because of its function as an intermediary for messages. The message conveyed by the message giver in this case is the teacher and recipient of the message or the student. The media in its implementation experienced several problems. This condition is also influenced by the class being taught. Regular classes and BIPA classes certainly have different treatments. The problem of media in the BIPA class is a serious matter to be considered by the instructor.